2009
DOI: 10.1130/b30041.1
|View full text |Cite
|
Sign up to set email alerts
|

The Tertiary evolution of the prolific Nanpu Sag of Bohai Bay Basin, China: Constraints from volcanic records and tectono-stratigraphic sequences

Abstract: The Bohai Bay Basin, located on the eastern Asian margin, is the second largest oil-production basin in China. It contains numerous depressions and sags, among which Nanpu Sag has become particularly important because of signifi cant oil discoveries in recent years. Geologically and tectonically, however, the rifting mechanism and geodynamic evolution of the basin remain uncertain. This paper uses detailed volcanic and stratigraphic records obtained through extensive drilling and sampling in Nanpu Sag to inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 41 publications
0
55
0
Order By: Relevance
“…These identified that sequence boundaries may not exactly correspond to the traditional lithostratigraphic or formation boundaries in these basins or subbasins. The ages of major sequence boundaries were determined from biostratigraphy (correlatable timeequivalent standard lacustrine fossil assemblages) and calibrated by paleomagnetic data and isotope ages of volcanic rocks (e.g., Wang and Qian, 1992;Yao et al, 1994;Song et al, 2003;Li, 2004;Qiu et al, 2006;Yang et al, 2006;Li, 2008;Yan et al, 2008;Liu et al, 2009;Zhang et al, 2009;Dong et al, 2010).…”
Section: Database and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These identified that sequence boundaries may not exactly correspond to the traditional lithostratigraphic or formation boundaries in these basins or subbasins. The ages of major sequence boundaries were determined from biostratigraphy (correlatable timeequivalent standard lacustrine fossil assemblages) and calibrated by paleomagnetic data and isotope ages of volcanic rocks (e.g., Wang and Qian, 1992;Yao et al, 1994;Song et al, 2003;Li, 2004;Qiu et al, 2006;Yang et al, 2006;Li, 2008;Yan et al, 2008;Liu et al, 2009;Zhang et al, 2009;Dong et al, 2010).…”
Section: Database and Methodsmentioning
confidence: 99%
“…This is attributed to the fact that these rifted lacustrine basins in east China are situated in the same tectonic setting, where similar age riftings and unconformities were developed because of the subduction of the West Pacific Plate and episodic upper-mantle upwelling (Li et al, 1997;Ren et al, 2002;. Also, the similar basin evolution episodes and tectonic history in these basins can be revealed by similar cyclic volcanic eruptions between basins, which represent different stages of continental rifting with specific age intervals (Chen et al, 1999;Song et al, 2003;Dong et al, 2010).…”
Section: Basin Characteristics and Types Of Basins In East Chinamentioning
confidence: 95%
“…Thus, we argue that these Cenozoic basalts were generated in an intra-continental setting associated with continental rifting in eastern China that might have been triggered by an asthenospheric mantle upwelling and partial melting. The episodic nature of the crustal uplift (Dong et al, 2010) and corresponding OIB-like volcanism in the Bohai Bay Basin area are also best explained by a lithospheric interaction with an upwelling asthenospheric mantle.…”
Section: Tectonic Setting and Geodynamic Implicationsmentioning
confidence: 97%
“…Age data used for calculating Sri and eNd is 40 Ma, 35 Ma and 23 Ma (Dong et al, 2010) for Cycle-1, -2 and -3 basalts.…”
Section: Petrography Of the Volcanic Rocksmentioning
confidence: 99%
“…Although there is a lack of written records of strong earthquakes due to the underdeveloped ethnic minorities, changes in the languages, natural hazards and ongoing wars between minority groups, the YYFZ has been speculated to have the greatest deformation and highest gradient of stress accumulation and thus to be the most likely location for potential catastrophic earthquakes because it is the main boundary fault between the active tectonic blocks of Xingan‐East Mongolia, Yanshan and Northeast China (Zhang et al, , ). Over the past several decades, its structural features (Liu et al, ; Shi et al, ; Su et al, ; Tian & Du, ; Tong, Yu, & Geng, ; Zhu et al, ), Mesozoic–Cenozoic evolution (Dong et al, ; Gilder et al, ; Hsiao et al, ; Huang et al, ; Xu & Zhu, ; Zhu, Niu, Xie, & Wang, ; Zhu, Zhang, Xie, Niu, & Wang, ), relationships between faults and basins (Allen, Macdonald, Xun, Vincent, & Brouet–Menzies, ; Chen et al, ; Chen & NĂĄbelek, ; Tang, Yang, Guo, & Tang, ; Yu, Min, Wei, Zhao, & Ma, ; Yu et al, ; Zhang et al, ; Zhang, Min, Deng, & Mao, ; Zhang et al, ; Zhou et al, ), potential oil and gas resources (Wang, ; Yang & Xu, ) and regional geodynamic processes (Fletcher, Fitches, Rundle, & Evans, ; Huang & Zhao, ; Ren, ; Ren, Lu, Li, Yang, & Zhuang, ; Ren, Tamaki, Li, & Zhuang, ; Wu, Xu, Zhu, & Zhang, ; Yin, ; Yin & Nie, ; Zhang, Zheng, Zheng, Wang, & Zhang, ; Zhao, ; Zhu, Chen, Wu, & Liu, ; Zhu et al, ) have been studied intensively. However, many controversial issues about the late Quaternary deformation of the YYFZ remain, especially with respect to its slip rate and the average recurrence interval of major earthquakes in the late Quaternary.…”
Section: Introductionmentioning
confidence: 99%